Chapter Leonardo in Romagna tra ritratti di città e scienza della guerra - CECCARELLI, FRANCESCO (Territori, 2023)
Leonardo's passage through Romagna in 1502 left significant traces in his graphic production, including the codex L and the celebrated map of Imola now at Windsor Castle. These records reveal his direct involvement in the political and military affairs of the region, as shown by the well-known concession letter issued to him by Cesare Borgia in 1502. The chapter presents a critical reexamination of the principal interventions to the fortifications of Cesena between 1502 and 1503, which were the focus of Leonardo's observations during his stay when Cesare Borgia tried to transform it into the capital of his ephemeral duchy.